2015
DOI: 10.1080/02786826.2015.1085953
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Monomer Size Distribution on the Radiative Properties of Black Carbon Aggregates

Abstract: Black carbon (BC), normally existing as aggregates, significantly affects the Earth radiative forcing, energy balance, and climate by scattering and absorbing both solar radiation and terrestrial emission. The BC particles are usually treated as fractal aggregates with same-sized monomers. However, experimental studies show that monomer diameters of BC normally obey a lognormal distribution ranging from 10 nm to over 100 nm. This study investigates the effects of monomer size distribution on the radiative prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…10 shows the effect of building an aggregate out of monomers with different radii. A similar study was already undertaken by Liu et al (2015) in which soot aggregates composed of 50 to 500 monomers with a 0 ∼ 33(45) ± 1.3(1.1) nm with , Q sca (shape, λ), κ(shape, λ), and the ratio of the latter to κ(sphere, λ) for a compact spherical grain with same mass. D f = 1.8 were considered.…”
Section: Mixed Monomer Size Effectsmentioning
confidence: 59%
See 1 more Smart Citation
“…10 shows the effect of building an aggregate out of monomers with different radii. A similar study was already undertaken by Liu et al (2015) in which soot aggregates composed of 50 to 500 monomers with a 0 ∼ 33(45) ± 1.3(1.1) nm with , Q sca (shape, λ), κ(shape, λ), and the ratio of the latter to κ(sphere, λ) for a compact spherical grain with same mass. D f = 1.8 were considered.…”
Section: Mixed Monomer Size Effectsmentioning
confidence: 59%
“…10 presents the case where there are only four monomers but of larger sizes: a 1 = 0.05 µm and a 2 = 0.1 or 0.5 µm. In the a 2 /a 1 = 10 case, the smallest monomers always represent less than 1% of the total aggregate volume for all the structures considered and in the a 2 /a 1 = 2 case, they represent 4 to 27% of the volume, proportions close to those in Köhler et al (2012) and Liu et al (2015). As in the two previous studies, both Q abs and Q sca are increased and the increase is larger when more small monomers are incorporated into the aggregate which can be likened to an increase of the monomer surface irregularity.…”
Section: Mixed Monomer Size Effectsmentioning
confidence: 92%
“…It can obtain the T‐matrix of multiple spheres from the T‐matrices of individual spheres by employing the addition theorem of vector spherical wave functions to account for mutual interaction among the system [ Mackowski and Mishchenko , ], and all information required for particle scattering and absorption properties can be derived from its T‐matrix. The popular and robust MSTM code developed and published by Mackowski and Mishchenko [] has been widely applied to obtain the optical properties of fractal aggregates [ Liu and Mishchenko , , ; Smith and Grainger , ; Liu et al ., ] and is used in this study. Meanwhile, the RDG assumes the monomers to be Rayleigh scatterers and ignores the intercluster multiple scattering [ Sorensen , ; Liu et al ., ].…”
Section: Methodology: Bc Geometries and Scattering Simulationsmentioning
confidence: 99%
“…Thus, more and more sophisticated geometric models are developed to study the optical properties of those nonspherical and inhomogeneous BC particles [ Chung et al ., ; Dong et al ., ]. For homogeneous cases, the aggregates with overlapping or dispersal monomers have been considered [ Bescond et al ., ; Liu et al ., ]. To account for the coating effects, a few complicated models with different mixing structures were built [ Liu et al ., ; Scarnato et al ., ; Dong et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et. al [30] proposed two different adjustments for the aggregates with particle size distribution, and found that the one using effective diameter, d ef f , is superior to the other. The scattering and absorption cross sections of aggregates with different-sized monomers are defined accordingly as…”
Section: Radiative Properties Of Nanoparticle Aggregatesmentioning
confidence: 99%